SIMULATING THE DRAG REDUCTION MODEL FOR A VEHICLE BY USING VORTEX GENERATOR (American International Journal of Sciences and Engineering Research, 2022)
Petroleum fuel consign has been lessening at a very high proportion. Almost all automobiles depend upon an IC engine driven by petroleum fuels. As much as the number of automobiles is developing in this modern world, it is obligated to reduce fuel expenditure. One of the ways to do this is to diminish the car's drag. Among a manifold process of reducing drag, using Vortex Generators is one. Delta-shaped vortex generators are used at the rear trunk of the range rover, where the flow separates. K-epsilon turbulent model in ANSYS-Fluent 19.2 software is used to imitate the airflows. This work observed the number and spacing between successive vortex generators based on comparing drag coefficient values. The contours of static pressure and velocity magnitude were also observed for each model. When the vortex generators were attached, the pressure coefficients at the rear trunk began to increase, confirming the increment in back pressure. Hence, the increase in back pressure indicates a reduction in the drag coefficient. It has been found that a combination of 7 vortex generators is the optimum solution. The devices work better at a higher velocity than the lower velocity without affecting vehicle stability. The vortex - 4 model's drag coefficient was found to be significantly lower than that of the standard model vehicle, which is 0.42877. The Base Model of Range Rover (2020) is my sense of humor, the highest drag coefficient. So vortex generators are commonly used on automobile vehicles to prevent downstream flow separation and improve their overall performance by reducing drag.JEL Classification Codes: C61, R41, Q51.